Description of land use in two rural properties in Cajá II, transassurini highway, Altamira-Pará (Research, Society and Development, 2022)
The survey was conducted in two properties located in the Cajá Citation II, Transassurini highway, in the month of August in the year 2006, during the first stage of the class of Agronomy 2006, aiming to characterize the different uses of land in these establishments. The families held deployments of annual crops such as rice, beans, maize and cassava. The owners use to prepare the ground the itinerant system. Notes on the two properties, that farmers use the same method to the planting of perennial crops and grassland management, the family I employ the system of grazing, as the owner prioritizes the preservation of soil and its nutrients. The ownership of the family II presents gallery preservation of forests, thereby maintaining the igarapés in good condition. The ownership of the family I has 20 hectares of virgin forest, while the ownership of the family II preserves approximately 73 hectares. In both the land lots of areas of grassland have to be compressed, due to frequent trampling of cattle.